2011 IEEE Nuclear Science Symposium Conference Record 2011
DOI: 10.1109/nssmic.2011.6153742
|View full text |Cite
|
Sign up to set email alerts
|

Device-less gating for PET/CT using PCA

Abstract: Movement degrades image quality in PET/CT. The first step in correcting for movement is to gate the data into dif ferent motion states. The gating is usually based on information from external devices, such as the chest position for respiratory movement, or an ECG signal for cardiac gating. Various groups have proposed methods to extract a gating signal out of the PET and/or CT data. Most of these methods are slow or require prior information (and associated tuning of parameters). Here we propose and evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 38 publications
2
118
0
1
Order By: Relevance
“…The correlation with the video-based method of approximately 0.8 for both resp_pca and resp_le as reported by Thielemans et al (11,28) could be achieved only with resp_le1sens/resp_pca1sens in the present study. Possible reasons for this discrepancy include the levels of sinogram compression that were used and the sampling rates of the respiratory signals, the latter of which were 5 times higher in this study.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The correlation with the video-based method of approximately 0.8 for both resp_pca and resp_le as reported by Thielemans et al (11,28) could be achieved only with resp_le1sens/resp_pca1sens in the present study. Possible reasons for this discrepancy include the levels of sinogram compression that were used and the sampling rates of the respiratory signals, the latter of which were 5 times higher in this study.…”
Section: Discussionsupporting
confidence: 60%
“…As PET and possibly MR data have to be gated retrospectively, exact knowledge of the corresponding respiratory state is required at any time point during the examination. Within the scope of this study, this was achieved by the acquisition of respiratory signals according to 5 methods, that is, the pressure-sensitive respiratory bellows (resp_bellows) that is shipped with the scanner by default, a prototype implementation of a self-gated MR imaging pulse sequence (resp_mr) (25,26), the PET-based sensitivity method (resp_sens) (9,10), and the application of dimensionality reduction techniques such as principal component analysis (PCA) or Laplacian eigenmaps to the sinogram space (resp_pca and resp_le, respectively) (11,27,28). Before execution of the PET-based methods, the list-mode streams were divided into nonoverlapping 200-ms time frames.…”
Section: Motion Correction Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that a respiratory signal can be extracted from raw PET list-mode data with principal component analysis (PCA) (12). If areas of sufficient contrast in the tracer uptake in a PET scan are moving, this movement will be detectable in the raw PET data.…”
Section: Pet-derived Signal Extractionmentioning
confidence: 99%
“…The surrogate signal for our motion model is a respiratory signal extracted using PCA from the raw PET data (Thielemans et al 2011); previously shown to provide similar information to an MR pencil-beam navigator to track breathing (Manber et al 2015). PET list-mode data are unlisted into short low spatial resolution sinogram frames.…”
Section: Pet Model Surrogatementioning
confidence: 99%